Optimized Design of Piled Embankment Using a Multi-Effect Coupling Model on a Coastal Highway - Aobo Zhang; Jin Liao; Zhen Liu; Cuiying Zhou; Lihai Zhang (Journal of Marine Science and Engineering, 2022)
This study presents a multi-effect coupling model to optimize the design of a geosynthetic-reinforced pile-supported embankment (GRPSE) considering the coupling effects of soil arching, membranes, and pile–soil interaction on a coastal highway. The developed model could optimize the design of the GRPSE to fulfill the design and construction requirements at a relatively low project cost. This was achieved by adjusting the critical factors that govern the settlement of GRPSEs, such as pile spacing, tensile stiffness of geosynthetic reinforcement (GR), arrangement of piles, pile cap size, and cushion thickness. The model predictions were validated by a series of field tests using a range of geotechnical sensors. The results show that model predictions agreed with experimental measurements reasonably well. In addition, the results indicate that in comparison to a square arrangement of piles, a triangle net arrangement can decrease the differential settlement of pile soil. Furthermore, this study demonstrates that a change in the GR’s tensile stiffness has little impact on the settlement of GRPSEs. This study can help to improve the stability of roadbeds of coastal highways.